Analysis Of Causes Of Jembrana Disease In Bali Cow And Prevention Measures - Jhon Firison; A Salim; Sudarmansyah Sudarmansyah; Alfayanti Alfayanti; Emlan Fauzi; Afrizon Afrizon; Andi Ishak (UNIVED Press, Dehasen University Bengkulu, 2022)
Jembrana disease is very detrimental to Balinese cattle breeders because it can cause rapid and sudden death of livestock in a relatively large area. Bengkulu Province is an area with the highest cases of Jembrana disease in Indonesia. This study aims to briefly explain the causes of Jembrana disease and its prevention efforts. The data collected is secondary data that is processed descriptively. The results of the analysis showed that Jembrana disease was caused by Lentovirus from the Retroviridae family. The clinical signs of this disease are mainly enlarged lymph nodes in the shoulders, front of the knees, and under the ears, as well as blood sweating in the back, inner thighs, abdomen, legs, and scrotum. Jembrana disease can be transmitted directly or indirectly through intermediaries. The most common risk factor for spreading is the uncontrolled movement of animals. The most recommended control and treatment are vaccination, counseling through communication, information and education and livestock traffic control. Breeders still need to control vectors and take biosecurity precautions such as maintaining the cleanliness of cages, equipment, places to eat and drink and administer vitamins